ANALISIS PENGENDALIAN KEJADIAN SALAH SISIP DOKUMEN REKAM MEDIS DI RUMAH SAKIT ISLAM IBNU SINA PEKANBARU TAHUN 2018 - ANASTASYA SHINTA YULIANA (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2018)
Control is an activity carried out to guarantee activities in accordance with the plan and if an error occurs, it can be corrected so that what is expected can be achieved. At the Ibnu Sina Islamic Hospital Pekanbaru the occurrence of misplaced medical record documents often occurs and the highest incidence occurs in January 2018 with 169 incidents. The purpose of the study is to analyze the control of the occurrence of misplaced medical record documents at Ibn Sina Islamic Hospital Pekanbaru. Research uses qualitative methods with the design of Rapid Assessment Procedures (RAP). The study was conducted on 01 June - 31 July 2018 at Ibnu Sina Islamic Hospital Pekanbaru. Informants in the study amounted to 6 people and the study used the Content Analysis model. The results showed that the lack of staff, the lack of special training, the absence of rewards for the best officers, lack of shelves, shelves made of wood and plywood, not displayed SOP (storage quality procedures and indicators), absence of microfile on documents thick medical records and the absence of a staff satisfaction survey in the storage section of medical record documents. It was concluded that controlling the occurrence of misplaced medical record documents had not been done optimally at Ibn Sina Islamic Hospital Pekanbaru. It is recommended to add additional officers, conduct special training, provide rewards for the best officers, increase the number of shelves, replace shelf shelves especially those with plywood, display SOPs (procedures and storage quality indicators), microfile on thick medical record documents and conduct satisfaction surveys officers in the storage section of medical record documents.